2021
DOI: 10.1029/2020jd033667
|View full text |Cite
|
Sign up to set email alerts
|

In Search of the Optimal Atmospheric River Index for US Precipitation: A Multifactorial Analysis

Abstract: Atmospheric rivers (ARs) are long, narrow filaments of enhanced water vapor transport that is typically associated with a low-level jet and extratropical cyclone (Ralph et al., 2018). When these moisture-laden ARs make landfall or penetrate inland, water vapor condenses and can release enhanced precipitation (e.g.,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…More restrictive climate thresholds, such as the 95th percentile, emphasized extreme AR events with limited occurrences, smaller affected areas, and shorter duration in the Arctic. These results were mostly consistent with the conclusions derived from the ARs making landfall on the US continents (C. Zhang et al, 2021). Furthermore, even though ERA5 had more AR events than MERRA-2.…”
Section: Ar Event Statisticssupporting
confidence: 89%
See 3 more Smart Citations
“…More restrictive climate thresholds, such as the 95th percentile, emphasized extreme AR events with limited occurrences, smaller affected areas, and shorter duration in the Arctic. These results were mostly consistent with the conclusions derived from the ARs making landfall on the US continents (C. Zhang et al, 2021). Furthermore, even though ERA5 had more AR events than MERRA-2.…”
Section: Ar Event Statisticssupporting
confidence: 89%
“…The AR detection and tracking algorithm followed a similar multifactorial design as C. Zhang et al (2021), in which we found that the choices of moisture fields and climate thresholds strongly dictated the summary statistics of the identified ARs and ARrelated surface hydrometeorological effects. In this work, we created six Arctic AR la-bels with each reanalysis dataset from January 1980 to December 2019.…”
Section: Ar Detection and Tracking Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…The wide variety of accepted detection algorithms in the AR research community creates a dilemma in determining the truth to compare this algorithm to for verification. Due to the lack of agreement between ARTMIP algorithms and the types of algorithms used to calculate ARs (Inda‐Díaz et al., 2021; Zhang et al., 2021), it is necessary to compare CG‐Climate to additional common tracking methods to best understand its reliability. We compare the output of CG‐Climate to eight different ARTMIP algorithms (Table 1).…”
Section: Methodsmentioning
confidence: 99%